Sensitivity of Tropical Insectivorous Birds to the Anthropocene: A Review of Multiple Mechanisms and Conservation Implications - Sherry, Thomas W. (Frontiers in Ecology and Evolution, 2021)
Insectivorous birds are declining widely, and for diverse reasons. Tropical insectivorous birds, more than 60% of all tropical birds, are particularly sensitive to human disturbances including habitat loss and fragmentation, intensive agriculture and pesticide use, and climate change; and the mechanisms are incompletely understood. This review addresses multiple, complementary and sometimes synergistic explanations for tropical insectivore declines, by categorizing explanations into ultimate versus proximate, and direct versus indirect. Ultimate explanations are diverse human Anthropocene activities and the evolutionary history of these birds. This evolutionary history, synthesized by the Biotic Challenge Hypothesis (BCH), explains tropical insectivorous birds’ vulnerabilities to many proximate threats as a function of both these birds’ evolutionary feeding specialization and poor dispersal capacity. These traits were favored evolutionarily by both the diversity of insectivorous clades competing intensely for prey and co-evolution with arthropods over long evolutionary time periods. More proximate, ecological threats include bottom-up forces like declining insect populations, top-down forces like meso-predator increases, plus the Anthropocene activities underlying these factors, especially habitat loss and fragmentation, agricultural intensification, and climate change. All these conditions peak in the lowland, mainland Neotropics, where insectivorous bird declines have been repeatedly documented, but also occur in other tropical locales and continents. This multiplicity of interacting evolutionary and ecological factors informs conservation implications and recommendations for tropical insectivorous birds: (1) Why they are so sensitive to global change phenomena is no longer enigmatic, (2) distinguishing ultimate versus proximate stressors matters, (3) evolutionary life-histories predispose these birds to be particularly sensitive to the Anthropocene, (4) tropical regions and continents vary with respect to these birds’ ecological sensitivity, (5) biodiversity concepts need stronger incorporation of species’ evolutionary histories, (6) protecting these birds will require more, larger reserves for multiple reasons, and (7) these birds have greater value than generally recognized.